Charles Withington and the Santa Fe Trail in North Lyon County - Don Schiesser (Symphony in the Flint Hills, 2012)
The road to Santa Fe opened in 1821. Four years later officials of the United States government met with members of the Osage tribe under the branches of an oak tree in what is now Council Grove to draw up a treaty providing for safe passage of wagons thr
Keywords: Charles Withington; Santa Fe Trail; Lyon County; Sac and Fox; Indians; gunsmith; tribe; Osage County; Council Grove; Kansas Territory; Buster Wheat; Pete Wheat; ranch; Fort Osage; Missouri; 142 Mile Creek; Neosho Valley; settlers; travelers; wagon; grass